2016
DOI: 10.1002/anie.201607885
|View full text |Cite
|
Sign up to set email alerts
|

Hydroformylation of Olefins by a Rhodium Single‐Atom Catalyst with Activity Comparable to RhCl(PPh3)3

Abstract: Homogeneous catalysts generally possess superior catalytic performance compared to heterogeneous catalysts. However, the issue of catalyst separation and recycling severely limits their use in practical applications. Single-atom catalysts have the advantages of both homogeneous catalysts, such as "isolated sites", and heterogeneous catalysts, such as stability and reusability, and thus would be a promising alternative to traditional homogeneous catalysts. In the hydroformylation of olefins, single-atom Rh cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
329
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 445 publications
(349 citation statements)
references
References 43 publications
19
329
0
1
Order By: Relevance
“…[2] Their cationic nature,m onoatomicity and defined coordination environment make oxide-supported SACs excellent candidates to bridge the gap between the disciplines of heterogeneous and homogeneous catalysis, [3] particularly in an umber of areas which have been traditionally dominated by molecular complex catalysts applied in solution. Hence, SACs have been recently explored for reactions classically catalyzed by cationic metal salts or complexes,i ncluding olefin hydroformylation, [5] olefin hydrosilylation, [6] alkyne hydrochlorination, [7] or C À Ccoupling. [8] Arelevant area where SACs can have aprofound impact is tandem catalysis,that is,the integration of two catalysts in as ingle pot to achieve sequential transformations in adirect manner.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Their cationic nature,m onoatomicity and defined coordination environment make oxide-supported SACs excellent candidates to bridge the gap between the disciplines of heterogeneous and homogeneous catalysis, [3] particularly in an umber of areas which have been traditionally dominated by molecular complex catalysts applied in solution. Hence, SACs have been recently explored for reactions classically catalyzed by cationic metal salts or complexes,i ncluding olefin hydroformylation, [5] olefin hydrosilylation, [6] alkyne hydrochlorination, [7] or C À Ccoupling. [8] Arelevant area where SACs can have aprofound impact is tandem catalysis,that is,the integration of two catalysts in as ingle pot to achieve sequential transformations in adirect manner.…”
Section: Introductionmentioning
confidence: 99%
“…The idea is then to target reactions typically performed by organometallic compounds in solution, and try to “heterogenize” the reaction using the same metal. Both Lang et al [66] and Wang et al [67] have demonstrated oxide supported Rh-SACs can catalyse hydroformylation of olefins as well as Rh-based homogeneous catalysts. In the latter case, the authors proposed an intriguing reaction pathway in which H 2 dissociation occurs at Rh adatoms leading to surface OH groups, which take part in the reaction with CO and propene coadsorbed at Rh 1 .…”
mentioning
confidence: 99%
“…It is thus demonstrated that this method could be employed to synthesize single atoms. Subsequently, they also proved that this method could be applied to prepare other metal atoms, such as single Ir atoms on FeO x and single Rh atoms on ZnO …”
Section: Synthesis Of Single‐atom Catalystsmentioning
confidence: 98%